Does Labor Protection Increase Support for Immigration? Evidence from Switzerland - Mirjam Bächli; Teodora Tsankova (Center for Economic Studies and ifo Institute (CESifo), 2021)
What affects native support for immigration? At a time of rising anti-immigration sentiments, this is a question raised by both academics and policy makers. We study the role of labor protection in shaping native preferences over migration policies. We look at Swiss national votes which took place from 2000 to 2014. Our results show that a higher immigrant exposure reduces pro-immigration vote shares in municipalities with a relatively low-skilled native population. The negative response is mitigated under higher levels of labor protection as measured by collective bargaining coverage. We look at labor market outcomes to understand mechanisms at play and find some suggestive evidence that collective agreements mitigate negative wage responses among low-skilled natives. Overall, the analysis suggests that labor protection affects vote outcomes by improving in addition other labor market conditions or by alleviating existing fears among the native population.
Keywords: D72; F22; J52; J61; 330; immigration; popular votes; collective bargaining